2019
DOI: 10.17977/um002v11i12019p090
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on Determinants of Energy Intensity in ASEAN Countries

Abstract: ASEAN is a region with a high level of economic growth. However, ASEAN region is also faced with several important issues in the energy sector such as high energy consumption growth, fossil energy dependency, and fluctuations in energy prices. Energy efficiency is viewed as the proper way to enhance energy security. The concept of energy intensity (ratio of energy consumption per GDP) is used to describe the level of energy efficiency. The objective of the research is to analyze factors that influence energy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Similarly, Wang and Han (2017) found the energy-intensity reducing effect of income on China's energy intensity, and Filipovic et al (2015) found the same for EU countries. The works of Belloumi and Alshehry (2018), Salim et al (2017), Fitriyanto and Iskandar (2019) and Chan et al (2019) obtained similar outcomes. However, Jones (1989Jones ( , 1991 reported income has a positive effect on energy intensity.…”
Section: Brief Literature Reviewmentioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, Wang and Han (2017) found the energy-intensity reducing effect of income on China's energy intensity, and Filipovic et al (2015) found the same for EU countries. The works of Belloumi and Alshehry (2018), Salim et al (2017), Fitriyanto and Iskandar (2019) and Chan et al (2019) obtained similar outcomes. However, Jones (1989Jones ( , 1991 reported income has a positive effect on energy intensity.…”
Section: Brief Literature Reviewmentioning
confidence: 54%
“…A threshold analysis by Yu et al (2022) provided mixed evidence regarding the effect of trade openness. For a group of ASEAN countries, Fitriyanto and Iskandar (2019) found trade openness increases energy intensity. Kwakwa and Adusah-Poku (2019) found trade openness reduces energy intensity in the South.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Based on research [6] stating that GDP has a negative relationship with energy intensity according to the Kuznets curve hypothesis, there is a non-linear (quadratic) relationship between energy intensity and GDP per capita. These results are supported by findings from various countries such as in the European Union in the study [7] that GDP has a significant negative impact on energy intensity.…”
Section: Discussionmentioning
confidence: 99%
“…These regulations and other forcing factors, such as energy price increases, have decreased energy intensity, as shown in Figure 3. Final energy intensity decreased, on average, by 2.8% per year from 2010 to 2017, exceeding the target of 1% per year (GOI 2014); as a result, Indonesia is ranked as having the third-lowest energy intensity among ASEAN members (Fitriyanto and Iskandar 2019). Successful pilot projects were then adapted to other municipalities, so the average electricity consumption of a streetlight system reduced from 20,589 kWh/year to 14,549 kWh/year, as shown in Figure 4.…”
Section: Policy Challenges In Indonesiamentioning
confidence: 93%